Vows & ruins : an epic romantic fantasy - Scheuerer, Helen (Scheuerer, Helen. Legends of Thezmarr, 2023)
Against all odds, Althea Zoltaire emerged from her trials as a champion. Now, she must train even harder and prepare herself to become a true warrior of Thezmarr. But Thea's world is turned upside down as she struggles to navigate her newfound magic and uncover the secrets of her past. Slowly, she begins to untangle the truth about her family, her powers and the evil that threatens to engulf the kingdom. When Wilder Hawthorne returns to be her official mentor, everything changes. Dark forces are gathering, and he will stop at nothing to prepare her for the challenges to come, even if it means breaking her. As war looms and their quest for answers leads master and apprentice deeper into danger, the undeniable connection between them intensifies - defying all odds, but also threatening to tear them apart. With secrets unravelling and evil closing in, Thea and Wilder fight to save the world, and each other. The fate of the realms rests in their hands - will they emerge victorious, or will the darkness consume them both? Full of action, adventure and steamy romance, this spellbinding fantasy will leave you breathless and begging for more.